Analysis of Corynebacterium silvaticum genomes from Portugal reveals a single cluster and a clade suggested to produce diphtheria toxin - Viana, Marcus Vinicius Canario; Galdino, José Henrique; Profeta, Rodrigo; Oliveira, Manuela; Tavares, Luís; de Castro Soares, Siomar; Carneiro, Paulo; Wattam, Alice Rebecca; Azevedo, Vasco (PeerJ, 2023)
Background Corynebacterium silvaticum is a pathogenic, gram-positive bacterial species that causes caseous lymphadenitis in wild boars, domestic pigs and roe deer in Western Europe. It can affect animal production and cause zoonosis. Genome analysis has suggested that one strain from Portugal and one from Austria could probably produce the diphtheria toxin (DT), which inhibits protein synthesis and can cause death. Methods To further investigate the species genetic diversity and probable production of DT by Portuguese strains, eight isolates from this country were sequenced and compared to 38 public ones. Results Strains from Portugal are monophyletic, nearly identical, form a unique cluster and have 27 out of 36 known Corynebacterium virulence or niche factors. All of them lack a frameshift in the tox gene and were suggested to produce DT. A phylogenetic analysis shows that the species has diverged into two clades. Clade 1 is composed of strains that were suggested to have the ability to produce DT, represented by the monophyletic strains from Portugal and strain 05-13 from Austria. Clade 2 is composed of strains unable to produce DT due to a frameshifted tox gene. The second clade is represented by strains from Austria, Germany and Switzerland. Ten genome clusters were detected, in which strains from Germany are the most diverse. Strains from Portugal belong to an exclusive cluster. The pangenome has 2,961 proteins and is nearly closed (α = 0.968). Exclusive genes shared by clusters 1 and 2, and Portuguese strains are probably not related to disease manifestation as they share the same host but could play a role in their extra-host environmental adaptation. These results show the potential of the species to cause zoonosis, possibly diphtheria. The identified clusters, exclusively shaded genes, and exclusive STs identified in Portugal could be applied in the identification and epidemiology of the species.
Keywords: Corynebacterium silvaticum; Pathogen; Diphtheria